The Director General of The Bulgarian National Radio and The Case of The Temporary Suspension of The National Programme "Horizon" - Nikolova, Raina (Yearbook of the Law Department, 2020)
The article comments on the administrative law issues related to the unprecedented suspension of the distribution of the national program “Horizon” of the Bulgarian National Radio on 13.9.2019, which caused the early termination of the mandate of the General Director of the media due to a gross violation of the principle of media services. As the person responsible for the programming policy of the public media service provider, the General Director is obliged to guarantee the citizens‘ right to information. Failure to fulfil this public duty is grounds for his removal from office.